Evaluation of canine tympanic membrane integrity using positive contrast computed tomography canalography - Alves-Nores, V.; Plested, M. J.; Rubial, R.; Salgüero, R. (Frontiers in Veterinary Science, 2024)
The assessment of the integrity of the tympanic membrane (TM) can be a diagnostic challenge in patients with otitis externa and/or otitis media (OM) under otoscopic examination. In computed tomography (CT), the TM is not always visualized. However, positive contrast canalography using conventional radiography has been previously described to evaluate the TM integrity. The aim of this single-centre study was to describe the positive contrast canalography technique in CT and its usefulness in identifying TM integrity in 11 dogs. Dogs with clinical signs of ear disease underwent CT canalography following a systematic protocol. Presence of contrast medium and contrast homogeneity within the tympanic cavity were assessed, confirming TM rupture when contrast medium was present in the tympanic cavity. CT canalography was performed in 16 ears and in 7/16 ears (44%) there was contrast in the tympanic cavity, confirming TM rupture (positive CT canalography result). In 2/7 cases (29%), rupture of the TM was identified in both otoscopic and CT canalography. In the remaining 5/7 (71%) positive CT canalography results, tympanic membrane rupture was identified only by CT canalography. In conclusion, positive contrast CT canalography is a complementary and safe technique to assess the TM integrity, with a potentially higher sensitivity than otoscopic examination for the diagnosis of TM rupture in dogs.